Selective attention for masked and unmasked emotionally toned stimuli: Effects of trait anxiety, state anxiety, and test order - Edwards, M.; Burt, J.; Lipp, Ottmar (John Wiley & Sons Ltd., 2010)
We investigated selective attention for masked and unmasked, threat, and positively valenced words, in high trait anxious (HTA) and low trait anxious (LTA) individuals using the emotional Stroop colour-naming task. State anxiety was varied within participants through the threat of electric shock. To investigate whether the sequencing of the state anxiety manipulation affected colour-naming latencies, the ordering of the shock threat and shock safe conditions was counterbalanced across participants. The results indicated that the ordering of the state anxiety manipulation moderated masked and unmasked threat bias effects. Specifically, relative to LTA individuals, HTA individuals showed a threat interference effect, but this effect was limited to those who performed under the threat of shock in the later stages of the experiment. Irrespective of exposure mode and state anxiety status, all individuals showed interference for threat in the early stages of the experiment, relative to a threat facilitation effect in the later stages of the experiment. For the unmasked trials alone, the data also revealed a significant threat interference effect for the HTA group relative to the LTA group in the shock threat condition, and this effect was evident irrespective of shock threat order. The results are discussed with respect to the automatic nature of emotional processing in anxiety. © The British Psychological Society.